The effect of integrating society, science, environment, technology, and collaborative mind mapping (ISSETCM2) model on mathematical literacy in terms of adversity quotient - Nur Hayati; Bambang Sri Anggoro; Khoirunnisa Imama (CV. FOUNDAE, 2022)
The implementation of this study aims to ensure the effectiveness of the Integrating Society, Science, Environment, Technology, and Collaborative Mind Mapping (ISSETCM2) learning model on mathematical literacy skills in terms of adversity quotient (AQ). This research design is quasi-experimental, with the population being all eighth-grade students in the academic year 2021/2022. The research sample was selected by cluster random. The average value of the mathematical literacy ability of the experimental class students is 72.03, and that of the control class is 50.34. Based on data interpretation and analysis of variance (ANOVA) of two-path unequal cells with a significant value of . The value of Sig is 0.001, so Sig . Based on the data, there are differences in the results of mathematical literacy skills between the learning model (ISSETCM2) and direct instruction learning models. Also, there are differences in adversity quotient categories (climbers, campers, and quitters) on mathematical literacy abilities. There is no interaction between learning model factors and adversity quotient on the results of students' mathematical literacy abilities. From these data, it can be concluded that there is an effect of the ISSETCM2 learning model on mathematical literacy skills in terms of the adversity quotient of class VIII. The research results show that each student has a different adversity quotient, which can affect students' mathematical reasoning abilities. For this reason, students need to know the adversity quotient to maximize their abilities.